(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Judging from the legislation appearance, China has built a civil judiciary sharing similar concepts and principles with western developed countries. Seeing through true judicial practice, however, one may find that legislation expectations are ignored or disobeyed so often that there seems to be other underlying rules controlling the civil judiciary in China. This article tends to show how the Case Quality Assessment System functions as one of the underlying rules shaping China’s civil judiciary by a comprehensive empirical survey on how the time limit for adjudication, one of the most important index in the assessment system, influences civil adjudication. The author found that in order to fulfil the assessment task, many irregular practices emerge, including haste adjudication, hidden over-time limit, and technical manipulation of statistics. These irregular practices are commonly implemented and have hindered healthy development of civil judiciary. Although legislation has made effort in changing the power balance between the court and the parties, it achieved little success due to the court’s urge of getting full control to deal with the assessment indexes. Focusing all attention onto the assessments, the court lacks interest for pursing procedural value, a value that needs to be reified through process rather than result and therefore is not reflected in assessment indexes. China has experienced hard time accepting procedural justice because of this. In addition, many procedural mechanisms cannot function properly because of the assessment system, such as pretrial, mediation, small claim procedure. It is impossible to develop a healthy civil judiciary in China without changing current adjudication assessment system.